Fir filter for makhraj recognition system - Aimi Nadia, Azmi (2010)
Audio and speech processing systems have steadily risen in importance in the everyday of most people in developed countries. Speech recognition is the process of converting an acoustic signal, captured by a microphone to a set of words. Recognition is generally more difficult when vocabularies are larger or have many similar-sounding words. There are some external parameters that can effects speech recognition system performance, including the characteristics of the environmental noise and the type and also the placement of the microphone. A particular objective of the invention is to recognize the correct makhraj pronounce for the recognition analysis using pre-processing data base Matlab. In this project, speech processing for makhraj recognition is built using Finite Impulse Response (FIR) filter. The speech that was collects all of data from respondent. It requires the simultaneously recording of the speech wave as many parameters as possible. Then, get the correct makhraj pronounce example (alif), (ba), (ta), (tsa), (jim), (ha) and others. After that, the project will built using Matlab software